Enhanced removal of heavy metals and phosphate in stormwater filtration systems amended with drinking water treatment residual-based granules. (15th February 2021) - Wang, Mengyue; Bai, Shunwen; Wang, Xiuheng
Abstract: To address the clogging issues in stormwater filtration systems, a drinking water treatment residual (DWTR)-based granule (DBG) substrate was developed herein by pyrolyzing and granulating the DWTR with bentonite and corncob. Toxicity characteristic leaching procedure studies indicated that fabricating into DBG stabilized the Al and heavy metals in DWTR and restrained the leaching risk. Then the removal performance of phosphate (PO₄-P) and heavy metal ions by the DWTR and DBG was evaluated in batch and laboratory-scale column experiments. Results from batch tests showed that the amount of Pb(Ⅱ) adsorbed by DBG (18.47 ± 0.56 mg g⁻ 1 ) was approximately 2.3 times of that adsorbed by DWTR (8.05 ± 0.19 mg g⁻ 1 ), whereas the PO₄-P adsorption capacity of DBG (8.63 ± 0.24 mg g⁻ 1 ) was much lower than that of DWTR (25.33 ± 0.81 mg g⁻ 1 ). This could be ascribed to the addition of corncob and bentonite (at a mass ratio of 20% and 40% in DBG, respectively), which provided extremely high cation exchange capacity for the Pb(Ⅱ) adsorption, while no effective PO₄-P adsorption component was involved. Moreover, the pyrolysis process could improve the Pb(Ⅱ) and PO₄-P adsorption capacity of the raw-mixture by 42% and 7%, whereas granulation process decreased those of the pyrolysis-mixture by 15% and 20%, respectively, owing to the reduction of accessible surface area in the DBG. Under various stormwater runoff conditions, the involvement of DBG in stormwater filtration systems exerted consistently fancy performance of Cu(Ⅱ), Pb(Ⅱ), Cd(Ⅱ) and PO₄-P removal, with average removal rates of over 86.20% and desorption rates of less than 3.50%, indicating irreversible and strong complexion between the contaminants and DBG. The DBG column manifested good permeability and stable hydraulic conductivity (2.74–2.52 m d⁻ 1 ) over a 54-day rainfall period, which was beneficial to address the clogging issue of DWTR. Overall, this study provides an alternative pathway to enhance the hydraulic condition and treatment performance of the stormwater filtration systems for urban runoff management. Graphical abstract: Image 1 Highlights: A granular drinking water treatment residual (DWTR)-based substrate was prepared. The DWTR-based granule (DBG) lowered the leaching toxicity of powdered DWTR. The DBG-amended bioretention achieved over 85% of phosphate and heavy metals removal. The column with DBG showed more stable hydraulic conductivity than that with DWTR. The adsorption mechanism of lead(Ⅱ) and phosphate to DBG was preliminarily discussed.